Severity Scoring Cutoff for MLPA and Its Diagnostic Yield in 332 North Indian Children with Developmental Delay - Srivastava, Priyanka; Kaur, Parminder; Daniel, Roshan; Chaudhry, Chakshu; Kaur, Anit; Seth, Saurabh; Kumari, Divya; Kaur, Anupriya; Panigrahi, Inusha (Journal of Pediatric Genetics, 2022)
Chromosomal aberrations/rearrangements are the most common cause of intellectual disability (ID), developmental delay (DD), and congenital malformations. Traditionally, karyotyping has been the investigation of choice in such cases, with the advantage of being cheap and easily accessible, but with the caveat of the inability to detect copy number variations of sizes less than 5 Mb. Chromosomal microarray can solve this problem, but again the problems of expense and poor availability are major challenges in developing countries. The purpose of this study is to find the utility of multiplex ligation-dependent probe amplification (MLPA) as a middle ground, in a resource-limited setting. We also attempted to establish an optimum cutoff for the de Vries score, to enable physicians to decide between these tests on a case-to-case basis, using only clinical data. A total of 332 children with DD/ID with or without facial dysmorphism and congenital malformations were studied by MLPA probe sets P245. Assessment of clinical variables concerning birth history, facial dysmorphism, congenital malformations, and family history was done. We also scored the de Vries scoring for all the patients to find a suitable cutoff for MLPA screening. In our study, the overall detection rate of MLPA was 13.5% (45/332). The majority of patients were DiGeorge's syndrome with probe deletion in 22q11.21 in 3.3% (11/332) followed by 15q11.2 del in 3.6% (12/332, split between Angelman's and Prader–Willi's syndromes). Also, 3.0% (10/332) of patients were positive for Williams–Beuren's syndrome 7q11.23, 1.8% (6/332) for Wolf–-Hirschhorn's syndrome 4p16.3, 1.2% (4/332) for 1p36 deletion, and 1% for each trichorhinophalangeal syndrome type I 8q23.3 duplication syndrome and cri du chat syndrome. The optimum cutoff of de Vries score for MLPA testing in children with ID and/or dysmorphism came out to be 2.5 (rounded off to 3) with a sensitivity of 82.2% and specificity of 66.7%. This is the largest study from India for the detection of chromosomal aberrations using MLPA common microdeletion kit P245. Our study suggests that de Vries score with a cutoff of 3 or more can be used to offer MLPA as the first tier test for patients with unexplained ID, with or without facial dysmorphism and congenital malformations.
Keywords: chromosomal aberrations; copy number variations; de Vries scoring; multiplex ligation-dependent probe amplification